Luke Wadding, the Irish Franciscans, and global Catholicism
1 online resource.
Keywords: "This book explores the endeavours and activities of one of the most prominent early modern Irishmen in exile, the Franciscan Luke Wadding. Born in Ireland, educated in the Iberian Peninsula, Wadding arrived in Rome in 1618, where he would die in 1657. In the "Eternal City", the Franciscan emerged as an outstanding theologian, a learned scholar, a diplomat, and a college founder. This innovative collection of essays brings together a group of international scholars who provide a ground-breaking analysis of the many cultural, political and religious facets of Wadding's life. They illustrate the challenges and changes faced by an Irishman who emerged as one of the most outstanding global figures of the Catholic Reformation. The volume will attract scholars of the early-modern period, early modern Catholicism, and Irish emigration"--